Answer:
see explanation
Step-by-step explanation:
(a)
Given
2k - 6k² + 4k³ ← factor out 2k from each term
= 2k(1 - 3k + 2k²)
To factor the quadratic
Consider the factors of the product of the constant term ( 1) and the coefficient of the k² term (+ 2) which sum to give the coefficient of the k- term (- 3)
The factors are - 1 and - 2
Use these factors to split the k- term
1 - k - 2k + 2k² ( factor the first/second and third/fourth terms )
1(1 - k) - 2k(1 - k) ← factor out (1 - k) from each term
= (1 - k)(1 - 2k)
1 - 3k + 2k² = (1 - k)(1 - 2k) and
2k - 6k² + 4k³ = 2k(1 - k)(1 - 2k)
(b)
Given
2ax - 4ay + 3bx - 6by ( factor the first/second and third/fourth terms )
= 2a(x - 2y) + 3b(x - 2y) ← factor out (x - 2y) from each term
= (x - 2y)(2a + 3b)
Answer:
X = 35.7 Y=54.3
Step-by-step explanation:
Let the 2 angles be called X and Y were X is the smaller angle
we know that both angles are complementary therefore
X+Y=90
X = Y - 18.6 ( Given )
Y - 18.6 + Y = 90 ( substitution)
2Y = 90 + 18.6
Y = 108.6/2
Y=54.3
X= Y-18.6= 54.3-18.6 = 35.7
Check : X + Y = 35.7+54.3=90
Answer:
the answer is the last one
Step-by-step explanation:
so the answer is d
Answer:
1/12πx3
Step-by-step explanation:
D on Edge
Answer:
96 km
Step-by-step explanation:
72/3 is 24. When yo add 24 to 72 you get 96km.